Comparison of efficiencies and costs of different weed control methods in paddy production in Iran - Tabatabaekoloor, Reza; Yousefnia pasha, Hasan; Hashemi, Jafar (International Journal of Agricultural and Biological Engineering, 2012)
Reza Tabatabaekoloor*, Hasan Yousefnia pasha, Jafar Hashemi (Department of Farm Machinery, Sari Agricultural Scieneces and Natural Resources University, Sari, Iran) Abstract: Using of efficient and inexpensive method for weed control has an important role in increasing efficiency and reducing costs of production. In this study, field experiments were carried out to evaluate the efficiency and costs of several weed control methods in paddy production during summer in Mazandaran, the north province of Iran in 2011. Seven weed control treatments (T1 to T7) were applied at three stages of rice growth (20 and 35 days after transplanting and grain harvesting time). Weed density, weed dry weight, labor used and economical comparison were determined in the basis of a complete randomized block design with three replications. Results showed that there were no significant differences among efficiencies of six treatments (except for weedy check method (T6) treatment). The minimum weed density and dry weight were obtained at herbicide+hand weeding once (T5) and herbicide application once (T7) treatments during all three stages. The costs of weed control were different among the treatments. Selection of control method has an important role in reducing labor. Hand weeding twice method (T1), because of its high weeding cost, hard work and worker restriction in the required time, is not useful. Powered weeding twice method (T2), due to its zero environment pollution, reducing costs of weed control and high benefit/cost, is the best and most appropriate treatment. Amount of weed damage in weedy check method (T6) varied between 30.5% and 45.3%. Keywords: weed control, paddy production, economic evaluation, mechanical weeding, chemical weeding, yield DOI: 10.3965/j.ijabe.20120502.004 Citation: Tabatabaekoloor R, Yousefnia pasha H, Hashemi J. Comparison of efficiencies and costs of different weed control methods in paddy production in Iran. Int J Agric & Biol Eng, 2012; 5(2): 28